FORMING OF METAPHORS WITH DENOTATIVE SEME “SIGN”AND DESCRIPTION OF LINGUISTIC WORLD (Scientific journal of the Fergana State University, 2023)
Metaphor is the existence of interrelations of human and the event of the universe. Language makes people be in relations with the reality. The national features of the reflection of the linguistic world are shown in metaphors. The special place is given to metaphors denoting the sign. The sign denoting metaphor can be formed both on the sign and object. Metaphors can be stray from their bases. As far as they are distant form their bases their metaphorical qualities increase.